PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD PADA MATA PELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR KELAS TINGGI - Azimah, Nurul; Suratno, Suratno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Research conducted to develop, test the feasibility, and measure the effectiveness of flashcard learning media in improving science and social science (Natural and Social Sciences) learning outcomes. The method used is Research and Development (R&D) following the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research subjects were class V of SDN Sekaran 01 Semarang with 28 students. The data collection techniques used were tests (pretest and posttest) and non-tests (observation, interviews, questionnaires). Data analysis techniques use normality test, t-test, and N-Gain test. The research results explain: (1) flashcard learning media was developed using the Canva application which contains a packaging display, front cover display, instructions for use display, information display, picture card display, and assignment display; (2) the results of the validity test of material experts, media experts, teacher responses, and student responses received the very appropriate category; (3) and effectiveness is shown from the results of the analysis of pretest and posttest scores. The t-test results have a sig value. (2-tailed) 0.000 <0.05. The N-Gain test result is 0.6067 in the medium category. In this research, it can be concluded that the development of Flashcard learning media has been successfully developed, is very feasible, and is effectively used to improve the science and science learning outcomes of class V students at SDN Sekaran 01 Semarang.